Book review: this is me! whatever you say - Wajdi, Majid; Pratiwi, Ni Kadek Anjelia Putri; Putra, I Komang Agus Januarta Sutisma; Amanah, Firda Maulia; Muhamadias, Nusrat; Amandari, Ni Kadek Pande Anggi (Journal of Language and Pragmatics Studies, 2023)
The purpose of writing is to convey to readers whether a book or work deserves a response from the public or not. Besides that, it is also to give considerations to other works of art such as plays, films, and a performance. Because the considerations conveyed by reviewers must be adjusted to the tastes of readers, a review published in a magazine may not be the same. The method we use in reviewing a book entitled "This Is Me" is the reporting method. The reviewers intentionally describe the contents of the book, and expresses the opinion through details that the reviewers select and omit. The reviewers would present the result of the review. This book has the benefit of encouraging readers of any age, whether young or old, to love themselves without having to worry about what other people think. Become a more confident person, and the story teaches the readers that even if someone falls and gets hurt, they have to do their best until it is time to heal. Such mental strength grows when one has the drive to make it even better. This book seems easy to understand because the language used by the author is light and contains many motivational sentences. This book really helps teenagers to believe more in their potential without worrying about other people's comments that harm them. This book manages to package the problem as well as the solution. There are case studies and motivational sentences that can encourage readers. The conclusion is if one feels that one cannot love him or herself, he or she does not know themselves deeply, and they still ignore other people's negative words. This book will guide the readers to solve the personal problems everyone is experiencing. By reading the book, it will make the readers or individuals can do various things without thinking about negative comments from other people.